Notice of a Stone Cist, Wooden Drinking Cup, and an old Dry Stone Dyke, found in Shetland (Proceedings of the Society of Antiquaries of Scotland, 1865)
This article is an account of the excavation of three sites in Shetland, at which he found a stone cist, a wooden drinking cup, and the remains of a dry stone dyke. Dimensions are provided for each of these finds and the circumstances of their discovery is noted.